2019
DOI: 10.32744/pse.2019.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The formation of personality safe type of conduct from pupils as one of the conditions of comfort of the educational environment

Abstract: Формирование личности безопасного типа поведения у школьников как одно из условий комфортности образовательной среды Актуальность проблемы обусловлена тем, что безопасность образовательной среды детских учреждений не только не теряет своей остроты, но и постоянно обостряется в связи с увеличивающейся информацией о случаях физического и психологического насилия в школах. Психолого-педагогическая безопасность образовательной среды связана с человеческим фактором. В школе это в первую очередь учителя и ученики. И… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…On the Internet, adolescents may encounter dangerous content, which include violence, aggression, pornography, materials promoting various forms of antisocial behavior, and destructive groups. In this regard, in our opinion, this research topic is currently relevant (Kodzhaspirov et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…On the Internet, adolescents may encounter dangerous content, which include violence, aggression, pornography, materials promoting various forms of antisocial behavior, and destructive groups. In this regard, in our opinion, this research topic is currently relevant (Kodzhaspirov et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…The flipped learning model transfers the delivery of knowledge into a student's private environment and allocates more time for practical skills. This strategy (Flipped Classroom) is comparatively new, developed by Jonathan Bergmann and Aaron Sams as a learning process model, filling the shortage of class hours for students majoring in physical education (Bergmann & Sams, 2012, 2014. Flipped learning creates opportunities to solve complex pedagogical issues in the education system.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the Health and Safety course taught for many years in school is to build children and adolescents' safe behavior skills, develop their knowledge and abilities to behave in an emergency correctly. However, safe behavior as personal demonstration is not developed only based on the information obtained (Kodzhaspirov et al, 2019). Previously, we showed that the educational process efficiency depends on teachers' abilities and possibilities to use all kinds of classes and learning activities (Polozova et al, 2017;Zimina et al, 2017).…”
Section: Introductionmentioning
confidence: 99%